THE INFLUENCE OF CURRENT RATIO ON STOCK PRICE IN MANUFACTURING COMPANIES IN MULTIPLE INDUSTRY SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD - Siska A. Siahaan; Fenny Krisna Marpaung (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to find out how the IDX's Current Ratio affects stock prices in manufacturing companies in various industrial sectors for three years, from 2018 to 2020. The company's financial statements and stock prices for the 2018-2020 period, use quantitative secondary data types. There are 11 business populations in this study. This study involves information on financial reports with a time series for the previous 3 years distributed from www.idx.co.id. sample for this study using purposive sampling. This study used a sample of 11 business actors from the previous three years, out of a total of 48 manufacturing business actors from various industries. Based on the findings of this study, stock prices are not significantly affected by the Current Ratio.